2015
DOI: 10.1038/aps.2015.76
|View full text |Cite
|
Sign up to set email alerts
|

Prednisone treatment inhibits the differentiation of B lymphocytes into plasma cells in MRL/MpSlac-lpr mice

Abstract: Prednisone treatment restricts B lymphocyte differentiation into plasma cells in MRL/lpr mice, which may be correlated with the inhibition of IL-21 production and the restoration of the balance between Blimp-1 and Bcl-6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 47 publications
(48 reference statements)
2
24
0
Order By: Relevance
“…Mtx was capable of controlling the inflammatory process as observed in Figure 1 ; it also provoked an increment of protein elimination in urine; this represents one of the collateral effects previously reported for the strain of mice used in this model [ 26 ] and this is what determines the deleterious capacity of Mtx on the nephron. The anti-inflammatory effect of Pdn also protected the nephrons from damage since proteinuria was not provoked, as has previously been reported in laboratory tests and clinical studies [ 27 , 28 ], where it has been suggested that Pdn has the capacity to improve the nephron function.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Mtx was capable of controlling the inflammatory process as observed in Figure 1 ; it also provoked an increment of protein elimination in urine; this represents one of the collateral effects previously reported for the strain of mice used in this model [ 26 ] and this is what determines the deleterious capacity of Mtx on the nephron. The anti-inflammatory effect of Pdn also protected the nephrons from damage since proteinuria was not provoked, as has previously been reported in laboratory tests and clinical studies [ 27 , 28 ], where it has been suggested that Pdn has the capacity to improve the nephron function.…”
Section: Discussionsupporting
confidence: 67%
“…Pdn managed to reduce articular inflammation of the joints caused by TMPD, however, was not able to control the increase in antinuclear autoantibodies titers. Some reports indicate that daily intragastric administration of Pdn at a dose of 2.5 mg/kg for three weeks blocked the increase of antinuclear autoantibodies titers associated with SLE development in MRL/lpr mice [ 28 ]; the Pdn treatment used in this assay did not have the capacity to modify the antinuclear autoimmune response, it can be considered that increasing the dose of this drug up to 5 mg/kg in this same treatment, it could generate a decrease in the antinuclear autoantibodies titers.…”
Section: Discussionmentioning
confidence: 99%
“…B cell subtypes, and the mechanisms of antibody production and maintenance, are highly diverse, and likewise the susceptibility of autoantibody-secreting plasma cells to therapies seems to be dependent on their tissue localization ( 1 ). Generally, conventional immunosuppressive therapy, using either steroids or cytostatic drugs, is commonly used in many autoimmune diseases and partly inhibits autoantibody production ( 2 5 ). At present, several drugs that specifically target B cells or plasma cells are either in clinical use or under development and promise to be very efficient for the treatment of various autoimmune diseases ( 6 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, GC induce apoptosis in B cells at all developmental stages (78–80). In addition, GC suppress plasma cell differentiation potentially via down-regulation of Blimp1 and Bcl6 (81, 82). Finally, GC may also directly affect the production of IgG antibodies through inhibition of activation-induced cytidine deaminase (AICDA), an enzyme required for class switch recombination and somatic hypermutation (83).…”
Section: The Mechanism Of Gc Action In the Treatment Of Slementioning
confidence: 99%